2017
DOI: 10.1103/physreve.96.012321
|View full text |Cite
|
Sign up to set email alerts
|

Optimal allocation of resources for suppressing epidemic spreading on networks

Abstract: Efficient allocation of limited medical resources is crucial for controlling epidemic spreading on networks. Based on the susceptible-infected-susceptible model, we solve an optimization problem as how best to allocate the limited resources so as to minimize the prevalence, providing that the curing rate of each node is positively correlated to its medical resource. By quenched meanfield theory and heterogeneous mean-field (HMF) theory, we prove that epidemic outbreak will be suppressed to the greatest extent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 42 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…assumed that the recovery rate is positively correlated with the average resource devoted to each infected individual and observed that the disease outbreak can be effectively eradicated, only when the amount of resource is above a critical value 24 . In addition, Chen 25 and Enyioha 26 presented a distributed resource allocation strategy to control an epidemic outbreak, respectively. Bottcher et al .…”
Section: Introductionmentioning
confidence: 99%
“…assumed that the recovery rate is positively correlated with the average resource devoted to each infected individual and observed that the disease outbreak can be effectively eradicated, only when the amount of resource is above a critical value 24 . In addition, Chen 25 and Enyioha 26 presented a distributed resource allocation strategy to control an epidemic outbreak, respectively. Bottcher et al .…”
Section: Introductionmentioning
confidence: 99%
“…The discrete particle swarm optimization technique was developed to optimize the local influence criterion for the independent cascade model [50]. Chen et al combined the perturbation theory with Lagrange multiplier method to derive the optimal allocation of the curing rates to suppress the epidemic spreading [31]. Lokhov and Saad used the dynamic message-passing approach for spreading processes and introduced an efficient, versatile and principled optimization framework for solving dynamic control resource allocation problems in spreading processes [26].…”
Section: Related Workmentioning
confidence: 99%
“…The identification of these "supernodes" is often done by employing the centrality index of the underlying network topology, such as betweenness, degree, pagerank, eigenvector, closeness, k-shell and Collective Influence etc [28], [29]. Another type of solution depends not just on the network topology, but also on the specific dynamics of the diffusion, including the Monte-Carlo (MC) methods, integer/linear programming, greedy algorithms and the message-passing algorithm [26], [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Countries with a higher resource level (economic or financial) could use stricter quarantine measures, while for countries with lower resources, the use of such measures led to the economic collapse, at least for a number of industries and/or social groups. The problem of strategy selection reduces to problems of optimal control theory for feedback systems [3][4][5] or to the theory of games in a more general case [6][7][8]. The use of one or another action strategy reduces to the classical problem of choice [9], i.e., to the definition of the sacrifice, when the salvation of someone or something is only possible at the expense of the other one.…”
Section: Introductionmentioning
confidence: 99%